Effects of cottonseed flour on testicular structure and sperm motility of rats - Timurkaan, N; Yilmaz, F; Risvanli, A; Timurkan, H; Karadas, E (Polish Soc Veterinary Sciences Editorial Office, 2005)
This study was undertaken to investigate the effect of cottonseed flour intake on sperm motility and pathological changes in testicular tissue in male rats. A total of 100 male rats were divided into 5 groups and each groups was fed with a diet containing cottonseed flour at a level of 0% (control), 5%, 10%, 20% and 40% for 80 days. Sperm motility of the rats and histopathological examination of their testicals were determined on days 20, 40, 60, and 80. Results indicated that sperm motility in rats fed with a diet containing containing 10%, 20%, and 40% cottonseed flour was significantly decreased. Clinical symptoms were evident only in rats fed with 40% cottonseed flour. Histopathological changes of varying severity in the testicular tissue of rats occured only in those fed with 10%, 20% and 40% of cottonseed flour. These changes included a decline in numbers of germinal layers, degeneration, desquamation, vacuolization of germinal epithelium, formation of intratubular giant cells, connective tissue proliferation in the intertubular area, and vacuolization of come leydig cells. The results of this study indicate that adding cottonseed flour exceeding a level of 5% to diets of rats decreased sperm motility and caused pathological changes in testicular tissue.
Keywords: cottonseed flour; testicle; sperm motility